Formulation, characterization and evaluation of morusin loaded niosomes for potentiation of anticancer therapy. Issue 57 (21st September 2018) - Agarwal, Srishti; Mohamed, M. Sheikh; Raveendran, Sreejith; Rochani, Ankit K.; Maekawa, Toru; Kumar, D. Sakthi
Abstract : Highly cytocompatible morusin-loaded niosomes were synthesized showing high drug loading and encapsulation efficiencies with sustained release of the drug. Enhanced therapeutic efficacy was observed against 4 different cancer cell lines. Abstract : Morusin, a water-insoluble prenylated flavonoid is known for its numerous medicinal properties. It manifests its anticancer potential by suppression of genes involved in tumor progression. However, poor solubility of the drug results in low bioavailability and rapid degradation thus hindering its clinical utilization. In order to overcome this, we have synthesized a niosome system composed of non-ionic surfactant span 60 and cholesterol using a thin-layer evaporation technique to improve the aqueous-phase solubility of the drug. Highly cytocompatible niosomes of 479 nm average size with smooth and uniform spherical morphology were synthesized in a facile manner. Unlike free morusin, nanomorusin was found to be freely dispersible in aqueous media. Having an extremely high drug entrapment efficiency (97%), controlled and sustained release of morusin resulting in enhanced therapeutic efficacy was observed in cancer cell lines of 4 different lineages. The results demonstrate that the morusin-niosome system is a promising strategy for enhanced anti-cancer activity against multiple cancer types and could be an indispensable tool for future targeted chemotherapeutic strategies.